Polycyclic aromatic hydrocarbons (PAHs) may explain the paradoxical effects of cigarette use on preeclampsia (PE). (15th May 2022) - Holme, Jørn A.; Valen, Håkon; Brinchmann, Bendik C.; Vist, Gunn E.; Grimsrud, Tom K.; Becher, Rune; Holme, Ane M.; Øvrevik, Johan; Alexander, Jan
Abstract: Tobacco smoking and use of snus (smokeless tobacco) are associated with adverse effects on pregnancy and neonatal outcomes. Nicotine is considered a key toxicant involved in effects caused by both smoking and snus, while pyrolysis products including polycyclic aromatic hydrocarbons (PAHs) in cigarette smoke represents the constituents most unequally divided between these two groups of tobacco products. The aim of this review was: i) to compare the impact, in terms of relative effect estimates, of cigarette smoking and use of Swedish snus on pregnancy outcomes using similar non-tobacco user controls, and ii) to examine whether exposure to PAHs from smoking could explain possible differences in impact on pregnancy outcomes. We systematically searched MEDLINE, Embase, PsycInfo, Web of Science and the Cochrane Database of Systematic Reviews up to October 2021 and identified studies reporting risks for adverse pregnancy and neonatal outcomes associated with snus use and with smoking relative to pregnant women with no use of tobacco. Both snus use and smoking were associated with increased risk of stillbirth, preterm birth, and oral cleft malformation, with comparable point estimates. These effects were likely due to comparable nicotine exposure. We also found striking differences. While both smoking and snus increased the risk of having small for gestational age (SGA) infants, risk from maternal smoking was markedly higher as was the reduction in birthweight. In contrast, the risk of preeclampsia (PE) was markedly lower in smokers than in controls, while snus use was associated with a slightly increased risk. We suggest that PAHs acting via AhR may explain the stronger effects of tobacco smoking on SGA and also to the apparent protective effect of cigarette smoking on PE. Possible mechanisms involved include: i) disrupted endocrine control of fetal development as well as placental development and function, and ii) stress adaption and immune suppression in placenta and mother.